Peningkatan Pemahaman Tentang Etika Pancasila Melalui Sosialiasi Pentingnya Membuang Sampah Pada Tempatnya Di Wilayah Pariwisata Pantai Air Manis Padang - Melisa Baitul Novia; Mutiara Gusliandini; Keke Kemala Dewi; Zaki Mubarak; Lara Sati; Dwi Puspita Putri; Reza Dwi Afrilla Yulanda; Panji Indra Lesmana; Muhammad Fajri; Nesa Dela Konceta; Satria Falih Ibrahim; Elwidarifa Marwenny; Eka Marayanti (CV. ITTC INDONESIA, 2025)
Air Manis Padang Beach is one of the popular beach attractions in West Sumatra. Apart from enjoying the natural panorama and waves, this beach cannot be separated from the legend of Maling Kundang. This sweet water beach has an unspoiled natural atmosphere. Plastic waste management in the Air Manis beach area aims to increase public awareness regarding the negative impact of plastic waste on the environment and the importance of maintaining beach cleanliness. Plastic waste management is a priority program based on the condition of the most abundant and frequently encountered piles of plastic waste. Therefore, local people and tourists will better understand the negative impact of plastic waste on the environment. And it can encourage a reduction in the amount of plastic waste that is thrown away carelessly, thereby reducing pollution in coastal areas. In this way, the beach will become more beautiful and attractive for tourists, thereby having a positive impact on the local tourism sector. The method used is an educational and participatory approach through socialization, discussions, quizzes activities, giving out door prizes. This research involved 10 respondents consisting of local communities, tourist visitors and tourism business actors. The research results show that this outreach increases public awareness and understanding of the importance of disposing of waste in the right place, as well as Pancasila ethical values such as environmental concern, social responsibility and shared awareness. This activity has a positive impact on the environment and quality of life of the surrounding community, as well as increasing awareness of the importance of environmental conservatio